Az ima szerepe a vallástanár mentális egészsége szempontjából - GORBAI, Gabriella Márta (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2016)
The Role of Prayer Regarding the Religion Teacher’s Mental Health. We consider that the main instrument of the teacher is his/her own personality, so it is his/her responsibility to take care of that instrument. A religion teacher should take care not only of his/her physical well-being, but also of his/her mental, emotional and spiritual one. In this study we point out the way prayers can influence the maintenance of health. Researches have proved that people who frequently pray are less likely to suffer from depression and anxiety; people who saw religion as being present in every aspect of their lives were less likely to be mentally ill than others. Only those who also prayed frequently had noticeably higher self-esteem; the relationship between mental health and religion is linked to the way people use prayer to deal with stress.